Platelets and endothelial dysfunction in gestational diabetes mellitus - Valero, Paola; Cornejo, Marcelo; Fuentes, Gonzalo; Wehinger, Sergio; Toledo, Fernando; van der Beek, Eline M.; Sobrevia, Luis [UNESP]; Moore-Carrasco, Rodrigo (Wiley, 2023)
The prevalence of gestational diabetes mellitus (GDM) has increased in recent years, along with the higher prevalence of obesity in women of reproductive age. GDM is a pathology associated with vascular dysfunction in the fetoplacental unit. GDM-associated endothelial dysfunction alters the transfer of nutrients to the foetus affecting newborns and pregnant women. Various mechanisms for this vascular dysfunction have been proposed, of which the most studied are metabolic alterations of the vascular endothelium. However, different cell types are involved in GDM-associated endothelial dysfunction, including platelets. Platelets are small, enucleated cell fragments that actively take part in blood haemostasis and thrombus formation. Thus, they play crucial roles in pathologies coursing with endothelial dysfunction, such as atherosclerosis, cardiovascular diseases, and diabetes mellitus. Nevertheless, platelet function in GDM is understudied. Several reports show a potential relationship between platelet volume and mass with GDM; however, platelet roles and signaling mechanisms in GDM-associated endothelial dysfunction are unclear. This review summarizes the reported findings and proposes a link among altered amount, volume, mass, reactivity, and function of platelets and placenta development, resulting in fetoplacental vascular dysfunction in GDM.
Keywords: diabetes mellitus; endothelium; gestational diabetes; platelet; pregnancy